2011
DOI: 10.15288/jsad.2011.72.199
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Smoking During Pregnancy and Risk of Alcohol Use Disorders Among Adult Offspring

Abstract: ABSTRACT. Objective: The aim of this study was to evaluate the association between maternal smoking during pregnancy (MSP) and lifetime risk for alcohol use disorder (AUD) and to explore possible mechanisms through which MSP may be related to neurobehavioral conditions during infancy and childhood, which could, in turn, lead to increased risk for AUD. Method: A sample of 1,625 individuals was followed from pregnancy for more than 40 years. Capitalizing on the long follow-up time, we used survival analysis to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 69 publications
0
7
0
1
Order By: Relevance
“…This paper adds further confirmation that MSDP is a risk factor for the offspring's smoking behaviors such as smoking initiation, regular smoking, and nicotine dependence. The risk of drug dependence among adolescent girls whose mothers smoked 10 or more cigarettes almost daily during pregnancy was raised as early as 1999 [9] and MSDP of ≥20 cigarettes per day has been also found to increase the risk of alcohol use disorder among offspring during a follow-up of 40 years [10]. Data from Finland have shown that MSDP is dosedependently associated not only with psychiatric comorbidities [11] and increased use of psychotropic medications [12] but also with all-cause mortality up to age 20 years [11].…”
mentioning
confidence: 99%
“…This paper adds further confirmation that MSDP is a risk factor for the offspring's smoking behaviors such as smoking initiation, regular smoking, and nicotine dependence. The risk of drug dependence among adolescent girls whose mothers smoked 10 or more cigarettes almost daily during pregnancy was raised as early as 1999 [9] and MSDP of ≥20 cigarettes per day has been also found to increase the risk of alcohol use disorder among offspring during a follow-up of 40 years [10]. Data from Finland have shown that MSDP is dosedependently associated not only with psychiatric comorbidities [11] and increased use of psychotropic medications [12] but also with all-cause mortality up to age 20 years [11].…”
mentioning
confidence: 99%
“…7, 1014, 15 Most epidemiological research has found robust statistical associations between SDP and substance-use problems in offspring when controlling for measured covariates, 4 which is consistent with a causal inference, although some studies suggest that these associations are accounted for by correlated risks. 1213 …”
mentioning
confidence: 99%
“…The study of Ekblad et al [5] found a relationship between MSP and ICD-10 diagnoses due to substance use, but as discussed earlier, these findings may be (partly) explained by incomplete adjustment for confounding factors. Nomura et al [50] found that the adult offspring of mothers who smoked 20 cigarettes a day or more were at greater risk for a lifetime diagnoses for alcohol use disorders, but the magnitude of the effect was modest. Fergusson et al [3] found no relationship with illicit substance use or dependency in late adolescence.…”
Section: Discussionmentioning
confidence: 99%